KEEFEKTIFAN MEDIA ANIMASI 2D UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI KPK & FPB - Soniya Agustin, Nabita; Sahari, Sutrisno; Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning media is very important as a tool that can help teachers deliver material. However, at SD Negeri Macana 1, the utilization of learning media is still not optimal, which has an impact on the low achievement of student learning outcomes. This study aims to determine the effectiveness of 2D Animation media to improve student learning outcomes in KPK & FPB math subjects. This research uses the type of R&D (Research and Delelopment) research with the ADDIE development model. The subjects of this study were fifth grade students of SD Negeri Macanan 1, totaling 28 students. Data collection techniques used observation, interviews, and evaluation questions. Data analysis techniques using descriptive quantitative data analysis. The results of this study indicate that from the results of the limited trial and the broad trial through working on evaluation questions, the completeness of student learning outcomes in the limited trial obtained a percentage score of 79.3% and the broad trial obtained a percentage score of 83.2%. Based on these results it can be concluded that 2D Animation media is very effective for improving student learning outcomes.